S120 Asthma in fire fighter applicants: burden of disease and factors predicting successful application. (15th November 2016) - Szram, J; Schofield, SJ; Fitzgerald, B; Cullinan, P
Abstract : Asthma is of concern to UK fire services that need to maintain maximal operational capability; current guidance suggests specialist respiratory review of applicants with a history of asthma, including tests of non-specific airway responsiveness. We present data from our occupational lung disease clinic over a 17 year period. Between March 1999 and January 2016, 112 firefighters were assessed; 90 of these completed histamine provocation testing allowing measurement of non-specific bronchial hyper-responsiveness using PC20 to histamine. Retrospective case note review was undertaken to look for predictors of PC20 from clinical history in this cohort. Subsequent follow up included recorded outcome of application and reported symptoms on future employment in the fire service. Unsurprisingly the majority of applicants were male (87.8%, n = 79) and atopic (78.6% n = 66). Around one third had experienced symptoms 27 (31.8) or taken treatment 32 (38.0) in the last year. Most patients were taking no asthma therapy at the time of assessment (64.4%, n = 58) with the majority of those on therapy taking a reliever only (n = 20, 22.2%). Three quarters (75.6%) had normal bronchial reactivity at the time of assessment (PC20 > 16 mg/ml histamine; n = 68) and 85.6% borderline normal airway responsiveness (PC20 > 8 mg/ml histamine; n = 77). Complete data on follow up was available for 86% of those assessed (n = 90); 64 of these had a recorded PC20. Table 1 shows the predictive factors for successful application in this cohort. Applicants were more likely to be rejected if they were older at time of application; reported recent asthma symptoms or use of treatment in the last year, had a history of childhood asthma or a measured PC20 of less than 16 mg/ml. The findings of this study suggest that a history of asthma in this occupational group remains a concern to occupational health teams focusing on operational capability of workforces with safety critical roles. Further follow-up of this cohort or a wider prospective study could provide applicants with asthma and their recruiters with useful guidance on individual suitability for employment as a fire fighter.